Permeability of Cork for Water and Ethanol - Fonseca, Ana Luisa; Brazinha, Carla; Pereira, Helena; Crespo, João G.; Teodoro, Orlando M. N. D. (Journal of Agricultural and Food Chemistry, 2013)
Transport properties of natural (noncompressed) cork were evaluated for water and ethanol in both vapor and liquid phases. The permeability for these permeants has been measured, as well as the sorption and diffusion coefficients. This paper focuses on the differences between the transport of gases? relevant vapors and their liquids (water and ethanol) through cork. A transport mechanism of vapors and liquids is proposed. Experimental evidence shows that both vapors and liquids permeate not only through the small channels across the cells (plasmodesmata), as in the permeation of gases, but also through the walls of cork cells by sorption and diffusion as in dense membranes. The present study also shows that cork permeability for gases was irreversibly and drastically decreased after cork samples were exposed to ethanol or water in liquid phase.
doi: 10.1021/jf4015729doi: 10.1021/jf4015729The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; diffusion; permeability; sealing properties; Sorption; water transport